The efficacy of a commercially available denture cleanser in decreasing candida albicans colonies on acrylic resin - Foronda, Pamela Joyce V.; Magtanong, Danilo (Adviser).
Part of the maintenance of dentures involves the employment of means for denture hygiene. In so doing, the development of pathologic conditions associated with denture wearing, of which denture stomatitis is the more common, may be avoided. Denture-wearers may use either mechanical or chemical means of cleaning their dentures or can use a combination of the 2. The aim of this study is to evaluate the efficacy of a commercially available denture cleanser (Polident*) in reducing the number of Candida albicans on acrylic resin. Thirty-four 1.5 cm2 acrylic resin pieces were divided equally into 2 groups, the control group (soaked in 0.12% chlorhexidine gluconate) and the experimental group (Polident* solution). One acrylic piece was soaked in sterile distilled water and served as the positive control for the experiment from which the initial count of Candida albicans was derived. Sampling was carried out on the acrylic surface from each group at the end of each assigned soaking time. The baseline count from the positive control was 131 colony-forming units (CFU's) of Candida albicans. The statistical test used showed that the null hypothesis, of there being no difference between the effect of treatment with 0.12% chlorhexidine gluconate (CHX) and with Polident* is accepted. It was also found that there was a 100% removal of the colonies on the acrylic resin using PolidentH at the recommended immersion time of 15 minutes. The results of this study-show that the efficacy of Polident^' is comparable with that of 0.12% CHX but there is not enough statistical evidence to conclude that it is more effective than 0.12% CHX in terms of reducing the number of Candida albicans on acrylic resin. Polident*' however, was indeed proven to be an effective denture cleanser because there was total elimination of the Candidal CFU's at the manufacturer's recommended immersion time of 15 minutes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentures; Denture cleansers